Pedagogy and Psychology as Sciences for the Formation of the Potential of Modern Society - Kirillova T. K., Burtseva E. V., Rak I. P., Karelin V. M., Ryspaeva C. K., Akhunzhanova M. K., Chukhrov A. S., Kruglova M. S., Sudakov O. V., Sudakov D. V., Sagitova V. R., Savina M. I., Smirnova O. G., Shutova N. V., Shutkina Z. A., Barsukov A. V., Polynskaya I. N., Potolokova M. O., Suvorova E. V., Kugai A. I., Petrova L. G., Shevchenko N. N., Elfimova A. V., Maslennikova S. F., Mezenina O. B., Medvedeva A. A. (Pedagogy and Psychology as Sciences for the Formation of the Potential of Modern Society, 2022)
the chapter deals with problems of the transformation of value-based landmarks of university education. The author demonstrated that changes in global interactions in political, economical and cultural spheres lead to transformations of the axiological dimension of the modern university. The key tendencies of this kind are historical and axiological de-ideologization, as well as maintenance of ecological mindset, as a sort of special format of ethical and epistemological approach to the world.
Keywords: ценности; higher education; экология; values; ecology; аксиология; философия образования; axiology; экологический университет; высшее образования; теория университета; ecological university; philosophy of education; theory of university